Controls on the occurrence and prevalence of floodplain channels in meandering rivers. Issue 3 (30th August 2016) - David, Scott R.; Edmonds, Douglas A.; Letsinger, Sally L.
Abstract: The process of channelization on river floodplains plays an essential role in regulating river sinuosity and creating river avulsions. Most channelization occurs within the channel belt (e.g. chute channels), but growing evidence suggests some channels originate outside of the channel‐belt in the floodplain. To understand the occurrence and prevalence of these floodplain channels we mapped 3064 km 2 of floodplain in Indiana, USA using 1.5 m resolution digital elevation models (DEMs) derived from airborne light detection and ranging (LiDAR) data. We find the following range of channelization types on floodplains in Indiana: 6.8% of floodplain area has no evidence of channelization, 55.9% of floodplains show evidence (e.g. oxbow lakes) of chute‐channel activity in the channel belt, and 37.3% of floodplains contain floodplain channels that form long, coherent down‐valley pathways with bifurcations and confluences, and they are active only during overbank discharge. Whereas the first two types of floodplains are relatively well studied, only a few studies have recognized the existence of floodplain channels. To understand why floodplain channels occur, we compared the presence of channelization types with measured floodplain width, floodplain slope, river width, river meander rate, sinuosity, flooding frequency, soil composition, and land cover. Results show floodplain channels occur when the fluvial systems are characterized by large floodplain‐to‐river widths, relatively higher meandering rates, and are dominantly used for agriculture. More detailed reach‐scale mapping reveals that up to 75% of channel reaches within floodplain channels are likely paleo‐meander cutoffs. The meander cutoffs are connected by secondary channels to form floodplain channels. We suggest that secondary channels within floodplains form by differential erosion across the floodplain, linking together pre‐existing topographic lows, such as meander cutoffs. Copyright © 2016 John Wiley & Sons, Ltd.